Analisis Kelayakan Investasi Pada Sektor Industri Jasa Sewa Alat Berat Menggunakan Skema Pendekatan BMC - Budiarjo, Akhmad; Syairudin, Bambang (Fakultas Ekonomi Universitas Gresik, 2023)
Accelerated development is a government strategy, this is done to reduce social inequality between regions. The government, through